Polyphenolic Nanomedicine Regulating Mitochondria REDOX for Innovative Cancer Treatment - Mingchuan Yang; Yufeng He; Qingqing Ni; Mengxue Zhou; Hongping Chen; Guangyun Li; Jizhong Yu; Ximing Wu; Xiangchun Zhang (MDPI AG, 2024)
Cancer remains a highly lethal disease globally. The approach centered on REDOX-targeted mitochondrial therapy for cancer has displayed notable benefits. Plant polyphenols exhibit strong REDOX and anticancer properties, particularly by affecting mitochondrial function, yet their structural instability and low bioavailability hinder their utility. To overcome this challenge, researchers have utilized the inherent physical and chemical characteristics of polyphenols and their derivatives to develop innovative nanomedicines for targeting mitochondria. This review examines the construction strategies and anticancer properties of various types of polyphenol-based biological nanomedicine for regulating mitochondria in recent years, such as polyphenol self-assembly, metal-phenol network, polyphenol-protein, polyphenol-hydrogel, polyphenol-chitosan, and polyphenol-liposome. These polyphenolic nanomedicines incorporate enhanced features such as improved solubility, efficient photothermal conversion capability, regulation of mitochondrial homeostasis, and ion adsorption through diverse construction strategies. The focus is on how these polyphenol nanomedicines promote ROS production and their mechanism of targeting mitochondria to inhibit cancer. Furthermore, it delves into the benefits and applications of polyphenolic nanomedicine in cancer treatments, as well as the challenges for future research.